Strengthening the Dayah Education Office in Aceh in Efforts to Prevent Sexual Harassment in Dayah from an Islamic Criminal Law Perspective - Magfirah, Anil; Razak, Abdur; Mustaqilla, Safira (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2025)
This study aims to analyze the role of the Aceh Dayah Education Office in preventing sexual harassment within Islamic boarding schools (dayah) from the perspective of Islamic criminal law. The focus of the study includes understanding the concept of sexual harassment in Islamic law, identifying the factors contributing to the rise of such cases in dayah, and formulating effective prevention strategies. The findings reveal that weak regulations, lack of supervision, and limited education are the main contributing factors. Therefore, strengthening the role of the Dayah Education Office through the revision of Qanun Aceh Number 6 of 2014 on Jinayah Law, enhancing the capacity of educators, establishing a safe and integrated complaint mechanism, and providing Islamic-based sexual education are strategic steps to create a safe and Sharia-compliant dayah environment.